Real-World Analysis of HRD Assay Variability in High-Grade Serous Ovarian Cancer: Impacts of BRCA1/2 Mutation Subtypes on HRD Assessment - Giovanni Luca Scaglione; Valentina Lombardo; Maurizio Polano; Giuseppa Scandurra; Angela Pettinato; Corrado Giunta; Rosario Iemmolo; Paolo Scollo; Ettore D. Capoluongo (Biomolecules)
The HRD (Homologous Recombination Deficiency) test is considered a genomic alteration useful for guiding therapeutic decisions in patients with ovarian cancer. Some commercial and in house alternative “academic” tests are available. Recent findings indicate that not all BRCA1/2 mutations determine the magnitude of HRD and that some patients carrying BRCA1/2 mutations may exhibit indeterminate or even negative HRD scores. Furthermore, certain therapies (e.g., olaparib and bevacizumab) offer particularly pronounced benefits for high-grade serous ovarian cancer (HGSOC) patients harboring mutations in the DNA-binding domain (DBD) of BRCA1/2. The aim of the present study is to investigate the relationship between the HRD scores and BRCA1/2 status of 51 HGSOC patients (50 BRCA1/2 mutated and 1 wild type). The HRD status was assessed by means of shallow whole-genome sequencing and BRCA1/2 status by the NGS pipeline. We did not find a correlation between the HRD status and type of BRCA1/2 alterations. A strong correlation between the HRD score and age was found. Our paper underlines the need to introduce other biological factors within the algorithms of the HRD evaluation in order to better tailor the HRD status, harmonize the metrics of the HRD assessment, and personalize therapies.